Diurnal variation of transitory starch metabolism is regulated by plastid proteins WXR1/WXR3 in Arabidopsis young seedlings - Zou, Wenjiao (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.